When Culture Meets Code: Enhancing E-Payment Technology Adoption Through QRIS in The Digital Transformation - Sari, Danar Retno; Sorongan, Erick; Kusno, Hendra Sanjaya (Innovation in Research of Informatics (Innovatics), 2025)
Bank Indonesia has implemented the National Non-Cash Movement (GNNT) to advance the payment system in Indonesia, focusing on safety and efficiency. The use of QRIS technology has accelerated transaction processes, reducing queues and increasing efficiency in various sectors. The electronic money component has seen significant growth, especially in non-bank institutions, with a rise in shopping transactions and the number of merchants. Trust in QRIS technology is high due to ease of use and secure transactions, supported by government regulations. This research investigates the factors influencing the adoption of QRIS (Quick Response Code Indonesian Standard) technology as an electronic payment system in Indonesia after the COVID-19 pandemic. The study focuses on the cultural dimensions of Power Distance (PD) and Uncertainty Avoidance (UA), and their influence on Trust and the Attitude to Use QRIS. A quantitative methodology using a questionnaire was employed, involving 103 active QRIS users, with analysis conducted using Structural Equation Modeling (SEM) via SmartPLS. Results show that Uncertainty Avoidance has a significant positive effect on Trust, which in turn significantly influences the Attitude to Use QRIS. However, Power Distance does not significantly impact Trust, suggesting that while government regulations are important, they do not directly enhance trust in the system. The findings highlight the importance of improving user confidence by reducing perceived risks and enhancing the security of the QRIS platform to foster wider adoption of cashless payments. Future research should explore the role of government policies in further detail to enhance user trust in digital payment systems.